CHIEF DEVELOPMENT TENDENCIES, STRUCTURAL CHANGES AND INNOVATIVENESS OF THE INDUSTRIAL AND SERVICE SECTORS IN POLAND - Dominiak, Joanna; Rachwał, Tomasz (Quaestiones Geographicae, 2016)
The goal of this article is to determine regularities concerning structural changes in the industrial and service sectors in Poland in the light of trends observable in the development of the world and national economies. The analysis embraces Poland in the years of the socio-economic transformation, but because of access to comparable data it focuses mainly on the years 2000–2014. Use is made of measures commonly applied in economic geography (employment, gross value added) and indicators based on them (mainly the structure and dynamics of change). First, the change in the role of the industrial and service sectors in the Polish economy as compared with other EU states is analysed in the light of the theoretical conceptions presented in the literature. Examined next are changes in the internal structure of the sectors and in the level of their innovativeness. The research showed there to be only slight changes in the role of the two sectors over the study period. Changes in the structure of the industrial sector tend towards its modernisation, which can signal steps taken for re industrialisation.